MENINGKATKAN MINAT BACA DAN KEMAMPUAN BAHASA INGGRIS ANAK MELALUI PEMBENTUKAN RUMAH BACA â€œENGLISH EXTENSIVE READINGâ€ - Wida Mulyanti; Lystiana Nurhayat Hakim (Universitas Perjuangan Tasikmalaya, 2021)
This community service is an English language learning program for elementary school-aged children in Kampung Cantilan, Desa Sukarame. This program is organized based on requests from parentsÂ who report that they want their children to learn English, but since KurikulumÂ 2013 (K-13) hasÂ been implemented, English is notÂ taught in ElementaryÂ School. It does notÂ belong to primary time allocation where it depends on the school policy to take EnglishÂ as an extracurricular subjectÂ or not. After conducting the interviews, it can be concluded that the parents want their children to learn English and the children have high motivation to learn English but lack of interest in reading books. Hence, thisÂ program is conductedÂ as a means for children to get access to learn English and to get motivated to read a lot. TheÂ method used in thisÂ community service programÂ was adapted from Vincent II (2009), namely community development practice, whereas theÂ steps used in providing training materials are: orientation, training, feedback and continuation. Pre-testÂ and post-testÂ are carried out at the beginning and at the end of the programÂ and show an increase in scores from pre-test to post-test.Â From the testÂ results,Â it can be concluded that this service contributes in gaining childrenâ€™s EnglishÂ language ability. Â Whereas from the interviews, it is known that the children's interest in reading has increased.